Progestins for pituitary suppression during ovarian stimulation for ART: a comprehensive and systematic review including meta-analyses. (30th September 2020) - Ata, Baris; Capuzzo, Martina; Turkgeldi, Engin; Yildiz, Sule; La Marca, Antonio
Abstract: BACKGROUND: Progestins are capable of suppressing endogenous LH secretion from the pituitary. Progestins can be used orally and are less expensive than GnRH analogues. However, early endometrial exposure to progestin precludes a fresh embryo transfer (ET), but the advent of vitrification and increasing number of oocyte cryopreservation cycles allow more opportunities for using progestins for pituitary suppression. OBJECTIVE AND RATIONALE: This review summarizes: the mechanism of pituitary suppression by progestins; the effectiveness of progestins when compared with GnRH analogues and with each other; the effect of progestins on oocyte and embryo developmental potential and euploidy status; and the cost-effectiveness aspects of progestin primed stimulation. Future research priorities are also identified. SEARCH METHODS: The Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE via PubMed, the Web of Science and Scopus were screened with a combination of keywords related to ART, progesterone, GnRH analogue and ovarian stimulation, in various combinations. The search period was from the date of inception of each database until 1 April 2020. Only full text papers published in English were included. OUTCOMES: Overall, the duration of stimulation, gonadotrophin consumption and oocyte yield were similar with progestins and GnRH analogues. However, sensitivity analyses suggested that progestins were associated with significantly lower gonadotrophin consumption than the long GnRH agonist protocol (mean difference (MD) = −648, 95% CI = −746 to −550 IU) and significantly higher gonadotrophin consumption than the short GnRH agonist protocol (MD = 433, 95% CI = 311 to 555 IU). Overall, live birth, ongoing and clinical pregnancy rates per ET were similar with progestins and GnRH analogues. However, when progestins were compared with GnRH agonists, sensitivity analyses including women with polycystic ovary syndrome (risk ratio (RR) = 1.27, 95% CI = 1.06 to 1.53) and short GnRH agonist protocols (RR = 1.14, 95% CI = 1.02 to 1.28) showed significantly higher clinical pregnancy rates with progestins. However, the quality of evidence is low. Studies comparing medroxyprogesterone acetate, dydrogesterone and micronized progesterone suggested similar ovarian response and pregnancy outcomes. The euploidy status of embryos from progestin primed cycles was similar to that of embryos from conventional stimulation cycles. Available information is reassuring regarding obstetric and neonatal outcomes with the use of progestins. Despite the lower cost of progestins than GnRH analogues, the mandatory cryopreservation of all embryos followed by a deferred transfer may increase cost per live birth with progestins as compared to an ART cycle culminating in a fresh ET. WIDER IMPLICATIONS: Progestins can present an effective option for women who do not contemplate a fresh ET, e.g. fertility preservation, anticipated hyper responders, preimplantation genetic testing, oocyte donors, double stimulation cycles.